Antiglycine receptor antibody and encephalomyelitis with rigidity and myoclonus (PERM) related to small cell lung cancer. (21st June 2013) - Kyskan, Robert; Chapman, Kristine; Mattman, André; Sin, Don
Abstract : A 39-year-old man (a lifetime non-smoker) presented with a locked left jaw and leg myoclonus. Clinical and electromyographic findings were in keeping with progressive encephalomyelitis with rigidity and myoclonus (PERM) syndrome. A thoracic CT scan demonstrated a 19 mm right hilar nodule, which was proven to be small cell lung cancer on bronchoscopic biopsy. Serological evaluation of the patient's plasma revealed antibodies against glycine receptors (serology negative for anti-GAD, anti-Yo, anti-Hu, anti-Ri, antiamphiphysin, anti-Ma2/Ta, anti-CRMP5 and anti-NMDA receptor). After his cancer was treated with chemotherapy and intravenous immunoglobulins (IVIg), neurological symptoms resolved but returned several months later without any evidence of cancer recurrence. Symptoms were refractory to corticosteroids and IVIg therapy. Rituximab was then initiated, which led to a dramatic and sustained resolution of symptoms. To our knowledge, this is the first case of PERM related to antiglycine receptor antibodies from paraneoplastic syndrome, which resolved with rituximab.